Credit - modular Training in Improving the Cognitive Competencies of students in an Ergonomic Aspect - Abdullayeva N.A. (Zien Journals, 2023)
The article presents the value of modular education at the university, which is expressed in the development of independent thinking under the guidance of a teacher. Ultimately, modular training enhances the cognitive and qualifying competencies of students.
Keywords: modular training; independent study of the subject; improvement of the student's cognitive competencies